Social Memory and Social Patterns Alterations in the Absence of STriatal-Enriched Protein Tyrosine Phosphatase - Blázquez, Gloria; Castañé, Anna; Saavedra, Ana; Masana, Mercè; Alberch, Jordi; Pérez-Navarro, Esther (Frontiers in Behavioral Neuroscience, 2019)
STriatal-Enriched protein tyrosine Phosphatase (STEP) is a neural-specific protein that opposes the development of synaptic strengthening and whose levels are altered in several neurodegenerative and psychiatric disorders. Since STEP is expressed in brain regions implicated in social behavior, namely the striatum, the CA2 region of the hippocampus, cortex and amygdala, here we investigated whether social memory and social patterns were altered in STEP knockout (KO) mice. Our data robustly demonstrated that STEP KO mice presented specific social memory impairment as indicated by the three-chamber sociability test, the social discrimination test, the 11-trial habituation/dishabituation social recognition test, and the novel object recognition test. This affectation was not related to deficiencies in the detection of social olfactory cues, altered sociability or anxiety levels. However, STEP KO mice showed lower exploratory activity, reduced interaction time with an intruder, less dominant behavior and higher immobility time in the tail suspension test than controls, suggesting alterations in motivation. Moreover, the extracellular levels of dopamine, but not serotonin, were increased in the dorsal striatum of STEP KO mice. Overall, our results strongly indicate that STEP deficiency disrupts social memory and other social behaviors as well as dopamine homeostasis in the dorsal striatum.